2004
DOI: 10.1124/jpet.104.075416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of CYP3A by HIV Protease Inhibitors

Abstract: Human immunodeficiency virus (HIV) protease inhibitors (PIs) are inhibitors of CYP3A enzymes, but the mechanism is poorly defined. In this study, time-and concentration-dependent decreases in activity as defined by maximum rate of inactivation (k inact ) and inhibitor concentration that gives 50% maximal inactivation (K I ) of CYP3A by amprenavir, indinavir, lopinavir, nelfinavir, ritonavir, and saquinavir were quantified using testosterone 6␤-hydroxylation as a marker for CYP3A activity with recombinant CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
203
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(218 citation statements)
references
References 41 publications
12
203
3
Order By: Relevance
“…The K s values obtained in this study agree well with the inhibition constant (K i ) of ritonavir for the CYP3A4-dependent metabolism of methadone, buprenorphine, and testosterone in human liver microsomes (20-50 nM (12, 13)). For other reactions catalyzed by microsomal CYP3A4, the K i for ritonavir varies from 0.10 to 0.38 μM (11,14,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The K s values obtained in this study agree well with the inhibition constant (K i ) of ritonavir for the CYP3A4-dependent metabolism of methadone, buprenorphine, and testosterone in human liver microsomes (20-50 nM (12, 13)). For other reactions catalyzed by microsomal CYP3A4, the K i for ritonavir varies from 0.10 to 0.38 μM (11,14,18).…”
Section: Resultsmentioning
confidence: 99%
“…The reactive intermediate(s) was proposed to involve the isopropyl-thiazole end-group (7), strictly required for potent CYP3A4 inhibition (9). Further, a noncovalent inhibitory complex, also known as a metabolic intermediate complex (MIC) (10), was reported to form during incubation of ritonavir with insect microsomes containing recombinantly expressed human CYP3A4 and cytochrome b 5 (11). Other studies indicated, however, that ritonavir acts as a competitive (12) or mixed competitive-noncompetitive CYP3A4 inactivator (5,13,14).…”
mentioning
confidence: 99%
“…The protease inhibitor ritonavir is among the most potent inhibitors of the CYP3A system [13]. Consequently, interaction of protease inhibitors with drugs that are cleared predominantly by CYP3A enzymes are profound and clinically significant [14].…”
Section: Introductionmentioning
confidence: 99%
“…CYP3A4 is most probably the one responsible enzyme in the degradation of indinavir as reviewed by Lin [57]. An aspect hampering the applicability of indinavir as precursor for a CYP3A4-specific breath test is the mechanism-based inhibition of CYP3A4 by indinavir [58]. Thus, in presence of indinavir the activity profiling for CYP3A4 is self-limited as indinavir actively decreases the CYP3A4 activity.…”
Section: Suitable Precursor Candidates From the Test Set?mentioning
confidence: 99%